ANALISIS PENGARUH STRUKTUR CORPORATE GOVERNANCE TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE DAN IMPLIKASINYA TERHADAP COST OF EQUITY CAPITAL (Studi Pada Perusahaan Sektor Pertambangan dan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 20 - Rahmat Putra Martua; Mohamad Nasir (Diponegoro Journal of Accounting, 2013)
The aims of this study were to analyze the impact of corporate governance structure such as accounting financial expertise, managerial ownership, institution ownership, foreign ownership, government ownership, and firm’s financial distress to corporate social responsibility disclosure and to see how it’s implication to cost of equity capital. This study used agency theory and signalling theory as the basic theories. Corporate social responsibility disclosure and cost of equity capital were chosen as the dependent variables because they had been used many times by previous studies. By using the purposive sampling method, samples of 195 firms were selected from public listed in the BEI. The data were analyzed using classical assumption test. Hypotheses were analyzed using the multiple linear regression model and single linear regeression model because this study used two model. The results of this study showed that accounting financial expertise, managerial ownership, institution ownership, foreign ownership, government ownership, and firm’s financial distress had a positif impact towards corporate social responsibility disclosure while foreign ownership, government ownership, and firm’s financial distress had a significant effect. On the other hand, corporate social responsibility disclosure had a negative significant impact towards cost of equity capital. Another variables such as size had positive significant impact towards corporate social responsibility disclosure.